2021
DOI: 10.1002/jcc.26738
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the substituent energy on the level of theory

Abstract: Most often, the substituent effects are described using rather troublesome Hammett constants. Quite recently, it has been proposed to use the so‐called substituent energy, which is based on total energies of the X‐substituted polycyclic aromatic hydrocarbon and phenyl. This article concerns the influence of the applied level of theory (i.e., both the basis set and the method) on the determined values of the substituent energies. For this purpose, the energies of the NH2 and NO2 groups in 16 unique positions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…It has recently been shown 14 that the X substituent energy is a convenient parameter to describe the proximity effect. For example, this parameter had a particularly high positive value for the nitro group substituted at the sterically unfavorable 4‐position of phenanthrene 14 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has recently been shown 14 that the X substituent energy is a convenient parameter to describe the proximity effect. For example, this parameter had a particularly high positive value for the nitro group substituted at the sterically unfavorable 4‐position of phenanthrene 14 .…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been shown 14 that the X substituent energy is a convenient parameter to describe the proximity effect. For example, this parameter had a particularly high positive value for the nitro group substituted at the sterically unfavorable 4‐position of phenanthrene 14 . Therefore, it should be particularly helpful in describing the influence of confinement in the in forms of the nX ‘iron maiden’ molecules on the energy of X.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The substituents in mono-substituted polycyclic aromatic hydrocarbons can only interact with adjacent hydrogen atoms. For the nitro and amino groups, it has been shown that their energies strongly depend on the effects of proximity [14,15]. Moreover, it was found that, in these systems, the energetic and geometric properties of the substituents are highly interdependent.…”
Section: Introductionmentioning
confidence: 99%